Instrumen Pengukuran Kelelahan pada Systemic Lupus Erythematosus - Bambang Aditya Nugraha; Gusgus Ghraha Ramdhanie (Journal of Telenursing (JOTING), 2023)
This study aims to identify instruments for measuring fatigue in SLE to manage this problem to improve quality of life. The method used is a narrative review by searching the EBSCO CINAHL and Pubmed databases with the keyword measurement instrument for fatigue, systemic lupus erythematosus. The results showed that there were 58 articles (CINAHL) and 27 articles from Pubmed, but only five pieces fit the focus of the study, which measured fatigue in SLE patients. In conclusion, Functional Assessment for Chronic Illness Therapy-Fatigue (FACIT-F), Fatigue Severity Scale (FSS), and fatigue pro are fatigue measurement instruments that can be used in SLE patients. Keywords: Fatigue Measurement Instrument, Systemic Lupus Erythematosus